Stereoselective Synthesis of Highly Functionalized Dispirooxindoles through [3+2] Cycloaddition of Carbonyl Ylides with 3‐Arylideneoxindoles. Issue 9 (9th February 2015) - Reddy, Basi V. Subba; Karthik, Govindaraju; Rajasekaran, Tamilselvan; Sridhar, Balasubramanian
Abstract: The three‐component coupling (3CC) of α‐diazoamide, aldehyde and 3‐arylideneoxindole using 5 mol‐% of Rh2 (OAc)4 is described to afford a novel class of dispirooxindole derivatives with complete regio‐ and stereoselectivity. It is a first report on the synthesis of natural product inspired libraries of dispirooxindoles through a carbonyl ylide cycloaddition. Abstract : A highly stereoselective synthesis of furo‐dispirooxindoles has been achieved by using 5 mol‐% of Rh2 (OAc)4 under mild conditions through 1, 3‐dipolar cycloaddition of 3‐arylideneoxindoles, with carbonyl ylides that are generated from 3‐diazooxindole and aldehyde.